Imago Rerum: dal rilievo alla ricostruzione digitale degli affreschi del Frigidarium di Pompei - D’Acunto, Giuseppe (Firenze Architettura, 2019)
From the etymological meaning of the term image and from its definitions in ancient times, the essay proposes a critical interpretation of the iconographical value of some ancient paintings from the area around mount Vesuvius. In particular the work focuses on the philological and digital reconstruction, carried out following iconographic and bibliographic references and the few remaining pictorial traces, of the cycle of frescos that decorated the cylindrical walls of the Frigidarium at the Stabian baths (Pompeii). These images, buried by the eruption of mount Vesuvius in the year 79 A.C., are presented here in their original configuration, through a projection immersed in their own environment.